2014
DOI: 10.1088/0004-637x/791/1/58
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Oxygen Abundances Across the Hertzsprung Gap

Abstract: We derived atmospheric parameters and spectroscopic abundances for C and O for a large sample of stars located in the Hertzsprung gap in the Hertzsprung-Russell diagram in order to detect chemical peculiarities and get a comprehensive overview of the population of stars in this evolutionary state. We have observed and analyzed high-resolution spectra (R = 60,000) of 188 stars in the mass range 2-5 M with the 2.7 m Harlan J. Smith Telescope at the McDonald Observatory including 28 stars previously identified as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…However, one exception is the recent extensive spectroscopic study of 188 Hertzsprung‐gap stars conducted by Adamczak & Lambert (), who concluded that their C and O abundances were almost similar to those of low mass dwarfs and no indication of significant mixing‐induced abundance changes was found. Therefore, their conclusion is in conflict with ours as well as those of other published work.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, one exception is the recent extensive spectroscopic study of 188 Hertzsprung‐gap stars conducted by Adamczak & Lambert (), who concluded that their C and O abundances were almost similar to those of low mass dwarfs and no indication of significant mixing‐induced abundance changes was found. Therefore, their conclusion is in conflict with ours as well as those of other published work.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the adopted stellar parameters and the resulting abundances in this study with those of Adamczak & Lambert (): (a) T eff , (b) log g , (c) v t , (d) v e sin i , (e) M , (f) [Fe/H], (g) [C/H], and (h) [O/H]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations